Application of Saccharomyces cerevisiae as a Probiotic for Producing Low Cholesterol and Antibiotic-Free Broiler Meat - Suci Wulandari; Theo Mahiseta Syahniar; Dadik Pantaya (Buletin Peternakan, 2020)
The aim of this study was to evaluate the application of S. cerevisiae as a probiotic for producing low cholesterol and antibiotic-free broiler meat. This study used 250 broilers (14 days old) which were divided into 5 treatment groups, those were T0 (rations without S. cerevisiae addition), T1, T2 and T3 (rations added with 0.5, 1, and 1.5 g/kg DM of S. cerevisiae respectively), and K group (commercial feed). Broilers were reared until 36 days old prior to slaughter. The carcass quality, abdominal fat, internal organs, cholesterol content of breast meat, the number of LAB and E. coli of intestinal tract were observed. The addition of S. cerevisiae tended to increase the number of LAB in intestinal tract, whereas the number of E. coli significantly decreased. The highest slaughter weight was found in group fed with commercial feed. There were no significant effects of S. cerevisiae addition on carcass, abdominal fat and weight of internal and immunity organs. The lowest cholesterol content was showed on broiler fed with rations added with 1 g/kg DM S. cerevisiae. Therefore it could be concluded that the addition of S. cerevisiae up to 1 g/kg DM rations showed health improvement and able to produce low cholesterol broiler meat.